A new species of Impatiens (Balsaminaceae) from Southern Xizang, China with supplementary knowledge on I. leptocarpa Hook. f. - Tian, Jing; Yuan, Tao-Hua; Peng, Shuai; Yang, Zhu-Zhu; Hu, Guang-Wan; Wang, Qing-Feng (Phytotaxa, 2024)
A new species, Impatiens lhunzeensis (Balsaminaceae), and a new record of I. leptocarpa from southern Xizang, China are reported and described in this study. Based on morphological and phylogenetic evidence, both I. lhunzeensis and I. leptocarpa are assigned to I. sect. Racemosae. The new species forms a clade with I. drepanophora, I. eubotrya and I. principis, while I. leptocarpa is phylogenetically close to I. radiata and I. harae. The new species has a sympatric distribution with and is morphologically similar to both I. radiata and I. harae, but differs by the hairy stem, the densely hairy leaf blade, the raceme inflorescence, the reniform dorsal petals, the navicular lower sepal, the broadly ovate to sub-orbicular upper petals and the triangular oblong lower petals.